Chapter Introduction Ethical agility in British contemporary dance technique - Colin, Noyale (Taylor & Francis, 2024)
In this extended introduction, Noyale Colin offers a rationale for the need to re-evaluate the concept of 'technique' and associated systems of training in contemporary dance. Colin proposes the concept of ethical agility as a way to engage with the challenges of twenty-first century dancing bodies. She begins by contextualising the nature and place of contemporary dance training in a shifting landscape of dance education. Drawing on affect and ethics theories, she argues that techniques in dance can be understood as relational techniques enabling a dialogical approach to teaching dance. She continues by discussing the ways that reflective and critical practice in dance training can help dancers to face the intensification of the eclectic 'supermarket' approach to body-training. With reference to issues of representation and inclusivity in dance training, the chapter theorises the potential of technique in dance training to be approached as an ethical embodied practice. It introduces key themes discussed in the co-edited volume such as the role of perception and internal attention, decision making, virtuosity, collaboration and enjoyment in dance training. Overall, it demonstrates that ethical concerns in contemporary dance can reveal the value of technique for forging transformation and creative cooperation and in turn developing active and critical dancers.